Los capitalismos emergentes en la nueva arquitectura internacional, ¿qué hay de nuevo en la división internacional del trabajo? - Palazuelos, Antonio (Papeles del Este, 2007)
In the last quarter century, China has spearheaded a true economic revolution, becoming a leading international player, to such an extent that world economic stability depends to a great extent on its economy. Among the factors that explain this spectacular economic growth we point out the high level o investment (supported by an increased savings rate and a strong FDI (foreign direct investment) entry) and the clear export nature of its production. Nevertheless, and despite its extraordinary success, the country faces numerous challenges and threats, such as consolidating the reforms undertaken, making economic growth compatible with social and environmental development or guaranteeing resources that permit maintaining growth in the long term. Despite the magnitude of transformation and the spectacular nature of results as well as the unmistakeable influence in the world economy, it is not easy to accept the fact that we are confronting a new phase in the international division of labor since to do so we need more knowledge of the events that are taking place both inside Chinese economy and society as well as on the international scene.